Sustainable community development in Ghana - Biney, Isaac Kofi; Boateng, John Kwame; Nixon, Paul G. (New York : Routledge, 2024)
This book explores sustainable community development in Ghana post-COVID-19, highlighting examples of how individuals facing extreme challenges have adapted to their changing circumstances. Through the voices of African researchers, it explores the different responses that local, subnational, and national stakeholders and communities initiated to preserve the gains made in achieving the Sustainable Development Goals in Ghana during the global pandemic. This collection considers how policy makers are tackling the pressing issues of sustainability, climate change and its effects on Africa and Ghana in particular, and multi-stakeholder policy responses to building communities in a post-COVID-19 world. The case studies show how communities are interacting to ensure sustainable community development and learning in the Global South, and the role that education and learning, both formal and informal, play in strengthening livelihoods, choices, and opportunities in African communities. An assessment of multi-stakeholder policy responses to building communities in Ghana, this book will be of interest to scholars and students in the field of Education, Education Management, Sociology, Economics, and African Studies. It will also be of interest to policy makers and practitioners engaged in community development programmes and activities and the development of associated policies.
Keywords: Sustainable Development Goals; Community development -- Ghana; Sustainable development -- Ghana; Education -- Ghana; COVID-19 Pandemic, 2020- -- Ghana -- Influence; BUSINESS & ECONOMICS / Development / Sustainable Development; EDUCATION / General